Essential macroeconomics : principles, cases, problems - Mansfield, Edwin (New York : W. W. Norton, 1998)
This book is divided into five parts: National output, Unemployment, and inflation; Fiscal policy and budget deficits; Monetary policy; Economic growth; and International economics.
Keywords: Macroeconomics; Macroeconomics